Analytical study and numerical simulation of diffusive prey predator model with Holling type II functional response. (May 2020) - Satria, A; Putri, A R; Syafwan, M
Abstract: A prey predator model which consists of two distinct population is discussed. The model used Holling response function of type II without limiting on prey population growth. Equilibrium points of the model was determined and stability of the model was analyzed by phase plane analysis. Furthermore, the model is reformulated by adding a diffusive terms to understand the spatial effect of the dynamical system behaviour. Solutions of the diffusive model were numerically illustrated with Neumann boundary conditions. Numerical simulations are presented to confirm the analytical results.